Irrigation improves weight-for-height z -scores of children under five, and women's and household dietary diversity scores in Ethiopia and Tanzania - Mekonnen, Dawit Kelemework; Choufani, Jowel; Bryan, Elizabeth; Haile, Beliyou; Ringler, Claudia (Wiley, 2022)
Evidence on the potential for agricultural intensification to improve nutrition has grown considerably. While small-scale irrigation is a key factor driving agricultural intensification in sub-Saharan Africa, its impact on nutrition has not yet been thoroughly explored. In this study, we assess the impact of adoption of small-scale irrigation in Ethiopia and Tanzania on household and women's dietary diversity, as well as children's nutrition. We use two rounds of primary data collected from irrigators and nonirrigators in Ethiopia and Tanzania. We used a panel fixed effects econometric approach to control for observed household, women and children specific characteristics as well as observed and unobserved time-invariant confounding factors. The results show that among Ethiopian households who reported having faced drought, women in irrigating households have higher Women's Dietary Diversity Score (WDDS) compared to women in nonirrigating households. In Tanzania, women in irrigating households have higher WDDS compared to nonirrigators and the impact of irrigation on WDDS more than doubles among households facing drought. In addition, among Tanzanian households who reported having faced a drought shock, irrigating households have higher Household Dietary Diversity Score compared to nonirrigators. Children in irrigating households in Ethiopia have weight-for-height z-scores (WHZ) that are 0.87 SDs higher, on average, than WHZ of children in nonirrigating households. In Tanzania, irrigation leads to higher WHZ-scores in children under-five among households who reported having experienced a drought in the 5 years preceding the survey. The study shows small-scale irrigation has a strong effect on households' economic access to food and on nutritional outcomes of women and children.